ANALISA PERILAKU KONSUMSI PERSPEKTIF EKONOMI ISLAM PADA MASYARAKAT DESA SIDOKERTO, KECAMATAN BUDURAN, KABUPATEN SIDOARJO - Qoriani, Hersa Farida (An-Nisbah: Jurnal Ekonomi Syariah, 2020)
The purpose of this study is to determine the consumption patterns of the majority of the population of Sidokerto Village, Buduran Subdistrict, Sidoarjo and to find out the factors that influence the consumption behavior patterns of Sidokerto villagers, Buduran Subdistrict, Sidoarjo. This type of research is a qualitative study using a case study approach study. The results of the study show that it is undeniable that with the increasing economic conditions in the family, the consumption patterns of the family of Indonesian Migrant Workers (TKI) in Sidokerto Village, Buduran District, Sidoarjo will change. There is a difference in consumption patterns before and after a family member who becomes a TKI (Indonesian Worker) abroad is becoming more consumptive. Where before there were family members who became migrant workers income was only enough to meet their daily food needs. The principles of consumption in Islam include several things, namely: the principle of justice, the principle of lawfulness, the principle of cleanliness, moral principles, the principle of generosity Keywords : Consumption, Sidokerto, Islamic Economics